Blood and body fluid exposure risks among health care workers: Results from the Duke Health and Safety Surveillance System - Dement, John M.; Epling, Carol; Østbye, Truls; Pompeii, Lisa A.; Hunt, Debra L. (American journal of industrial medicine, 2004)
Background Health care workers (HCWs) are at risk of exposures to human blood and body fluids (BBF). Needlestick injuries and splashes place HCWs at risk for numerous blood‐borne infections including human immunodeficiency virus (HIV), hepatitis B (HBV), and hepatitis C (HCV). Utilizing a new comprehensive occupational health surveillance system, the objective of this research was to better define the BBF exposure risk and risk factors among employees of a large tertiary medical center. Methods A population of 24,425 HCWs employed in jobs with potential BBF exposures was followed for BBF exposure events from 1998 to 2002. BBF exposure rates were calculated for strata defined by age, race, gender, occupation, work location, and duration of employment. Poisson regression was used for detailed analyses of risk factors for BBF exposure. Results The study population reported 2,730 BBF exposures during the study period, resulting in an overall annual rate of 5.5 events/100 FTEs and a rate of 3.9 for percutaneous exposures. Higher rates were observed for males, persons employed less than 4 years, Hispanic employees, and persons less than 45 years of age. Much higher rates were observed for house staff, nurse anesthetists, inpatient nurses, phlebotomists, and surgical/operating room technicians. Poisson regression results strengthened and extended results from stratified analyses. Rates of percutaneous exposures from hollow needles were found to decrease over the study period; however, exposure rates from suture needles appear to be increasing. Conclusion While continued training efforts need to be directed toward new HCWs, our data also suggest that employees who have been in their job 1–4 years continue to be at higher risk of BBF exposures. This research also points to the need for better safety devices/products and work practices to reduce suture‐related injuries. Am. J. Ind. Med. 46:637–648, 2004. © 2004 Wiley‐Liss, Inc.